Direct oral anticoagulants: unique properties and practical approaches to management. Issue 20 (11th July 2016) - Barnes, Geoffrey D; Kurtz, Brian
Abstract : Since 2009, four direct oral anticoagulants (DOACs) have been introduced for treatment of venous thromboembolism and stroke prevention in non-valvular atrial fibrillation. While they are currently first-line therapy for a majority of patients, there are a number of clinical situations where warfarin is preferable. In both randomised trials and real-world populations, use of DOACs significantly reduces the risk of intracranial haemorrhage as compared with warfarin. While drug-specific reversal agents are currently only available for dabigatran, andexanet alpha is pending approval for reversal of factor Xa inhibitors, reducing concerns about major bleeding for many patients and providers. DOACs can be held for 2–4 days prior to a procedure, depending on a patient's renal function, but should not be restarted too rapidly post-procedurally given their fast time to peak activity (∼2 hours). The anticoagulation clinic should play an important role in managing patients on all oral anticoagulation, both warfarin and DOACs.